PENGARUH PELABUHAN SEBAGAI SIMPUL PERTUMBUHAN TERHADAP PENGEMBANGAN WILAYAH STUDI KASUS : PELABUHAN PAELANGKUTA NUSANTARA RAHA - Sitti Astija; Ardiana Yuli Puspitasari (Universitas Islam Sultan Agung Semarang, 2017)
ABSTRACTMuna is an archipelago in Southeast Sulawesi, so as to distribute the crops and the potential of the region in Muna are more optimal by using of sea transportation. The port is expected to support the activities of loading and unloading of goods, up and down the passenger activities, so that the ship visits activity took place smoothly. On the other hand the port has a function of interface, meaning that it provides a variety of facilities and services which is required for transferring from ship to the land transportation and move goods from one ship to others. Node port terminal growth Paelangkuta Raha archipelago is a port-type collector. The port terminal is used as transportation among regions within the province or interprovincial. As well as being a place of transporting goods distribution services in the area of Muna Regency universal. The purpose of this study was to know the Influence of growth Node of Port Paelangkuta Raha toward Muna Regional development. To achieve these objectives, quantitative research in rationalistic approach is used in this research by using a simple linear regression analysis using SPSS16 application. Regional development made possible by the central growth which is based on the development of human resources and natural resources, both types of resource development takes place so that raises the flow of goods. Raw material is transported from producing areas to the plant site and the goods results are transported from producer to consumer. The findings from this research is that the growth Node of Port Paelangkuta Raha Muna affect the development area. Keywords: Node, Growth